Degradation of Southeast Asian tropical peatlands and integrated strategies for their better management and restoration. Issue 7 (17th May 2021) - Mishra, Shailendra; Page, Susan E.; Cobb, Alexander R.; Lee, Janice Ser Huay; Jovani‐Sancho, Antonio Jonay; Sjögersten, Sofie; Jaya, Adi; Aswandi,; Wardle, David A.
Abstract: About half of the world's tropical peatlands occur in Southeast (SE) Asia, where they serve as a major carbon (C) sink. Nearly 80% of natural peatlands in this region have been deforested and drained, with the majority under plantations and agriculture. This conversion increases peat oxidation which contributes to rapid C loss to the atmosphere as greenhouse gas emissions and increases their vulnerability to fires which generate regional smoke haze that has severe impacts on human health. Attempts at restoring these systems to mitigate environmental problems have had limited success. We review the current understanding of intact and degraded peatlands in SE Asia to help develop a way forward in restoring these ecosystems. As such, we critically examine them in terms of their biodiversity, C storage, hydrology and nutrients, paying attention to both above‐ground and below‐ground subsystems. We then propose an approach for better management and restoration of degraded peatlands that involves explicit consideration of multiple interacting ecological factors and the involvement of local communities who rely on converted peatlands for their livelihood. We make the case that as processes leading to peatland development involve modification of both above‐ground and below‐ground subsystems, an integrated approach that explicitly recognizes both subsystems and their interactions is key to successful tropical peatland management and restoration. Synthesis and applications . Gaining a better understanding of not just carbon stores and their changes during peat degradation, but also an in‐depth understanding of the biota, nutrient dynamics, hydrology and biotic and abiotic feedbacks, is key to developing better solutions for the management and restoration of peatlands in Southeast Asia. Through the application of science‐ and nature‐based solutions that recognize the interactions among the above‐ground and below‐ground subsystems, and taking into account the livelihood needs of local people, we propose a way to mitigate the ongoing environmental damage that is occurring in these iconic and unique ecosystems. Abstract : Gaining a better understanding of not just carbon stores and their changes during peat degradation, but also an in‐depth understanding of the biota, nutrient dynamics, hydrology and biotic and abiotic feedbacks, is key to developing better solutions for the management and restoration of peatlands in Southeast Asia. Through the application of science‐ and nature‐based solutions that recognize the interactions among the above‐ground and below‐ground subsystems, and taking into account the livelihood needs of local people, we propose a way to mitigate the ongoing environmental damage that is occurring in these iconic and unique ecosystems. Abstrak: Sekitar setengah dari lahan gambut tropis dunia berada di Asia Tenggara, dan gambut tersebut berfungsi sebagai penyimpan utama karbon. Hampir 80% dari lahan gambut alami di wilayah Asia Tenggara ini telah mengalami deforestasi dan dilakukan drainase, sebagian besar untuk perkebunan dan pertanian. Perubahan tersebut meningkatkan oksidasi gambut yang selanjutnya berkontribusi terhadap hilangnya karbon secara cepat ke atmosfer sebagai emisi gas rumah kaca, dan meningkatkan kerentanannya terhadap kebakaran yang menghasilkan kabut asap dan berdampak sangat buruk terhadap kesehatan. Upaya memulihkan ekosistem ini untuk mengurangi masalah lingkungan belum sepenuhnya berhasil. Kami mengkaji pemahaman terkini tentang lahan gambut alami dan gambut terdegradasi di Asia Tenggara untuk membantu mengembangkan cara untuk memulihkan ekosistem ini. Karena itu, kami secara kritis mempelajari dalam kaitannya dengan keanekaragaman hayati, penyimpanan karbon, hidrologi dan unsur hara, dengan memperhatikan subsistem di atas dan di bawah tanah gambut. Kami kemudian mengusulkan pendekatan pengelolaan lahan gambut yang lebih baik dan restorasi lahan gambut terdegradasi yang melibatkan pertimbangan dari berbagai faktor ekologi yang saling berkaitan serta keterlibatan masyarakat lokal yang tergantung pada lahan gambut untuk mata pencaharian mereka. Kami berpendapat bahwa karena proses pada pengembangan lahan gambut melibatkan perubahan subsistem di atas dan di bawah tanah gambut, pendekatan terintegrasi yang secara eksplisit mengakui kedua subsistem dan interaksinya adalah kunci keberhasilan pengelolaan dan restorasi lahan gambut tropis. Sintesis dan aplikasi . Memperoleh pemahaman yang lebih baik tidak hanya tentang simpanan C dan perubahannya selama degradasi gambut, tetapi juga pemahaman mendalam tentang biota, dinamika hara, hidrologi serta aspek biotik dan abiotik, adalah kunci untuk mengembangkan solusi yang lebih baik untuk pengelolaan dan restorasi lahan gambut di Asia Tenggara. Melalui penerapan solusi berbasis ilmu pengetahuan yang mempertimbangkan interaksi antara subsistem di atas dan di bawah tanah, dan dengan mempertimbangkan kebutuhan mata pencaharian masyarakat lokal, kami mengusulkan cara untuk mengurangi kerusakan lingkungan yang terjadi pada di ekosistem lahan gambut yang bersifat ikonik dan unik ini.